Penguatan Kapasitas UMKM melaPENGUATAN KAPASITAS UMKM MELALUI PENDAMPINGAN BERBASIS PLUT-KUMKM DI KABUPATEN GORONTALOlui Pendampingan Berbasis PLUT-KUMKM di Kabupaten Gorontalo - Tabo, Sarfan; Nuna, Muten; Podungge, Abdul Wahab; Junus, Dikson; Napir, Suaib; Hunawa, Robby; Sahi, Nirmala A.; Pauweni, Lisnawati; Walahe, Dewi; Harun, Nur Istiyan; Polinggapo, Jefri; Arsjad, Muh. Fachri; Hasan, Silvana; Bilondatu, Nikma; Biongan, Ahiar; Polapa, Lianti; Hadi, Amelia; Banum, Alfan; Andara, Isnauril (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2026)
PLUT-KUMKM plays a strategic role in strengthening the capacity and empowering MSMEs through business mentoring, business consulting, legal facilitation, and marketing network development. Community service through a student internship program at PLUT-KUMKM Gorontalo Regency is a collaboration between universities and the local government to increase the capacity of MSMEs while providing practical experience for students. This activity aims to support business strengthening through administrative assistance, legal facilitation, and product promotion and marketing. The method used is a participatory approach by directly involving students in services and mentoring. Data was collected through observation, direct involvement, business administration management, and documentation. The results of the activity show a real contribution, namely mentoring approximately 25 MSMEs, facilitating NIB and halal certification for approximately 15 MSMEs, as well as support for entrepreneurship training, marketing, and MSME talk shows. This collaboration has had a positive impact and needs to be strengthened continuously.